Validation of a Vitamin D Specific Questionnaire to Determine Vitamin D Status in Athletes - Larson-Meyer, D. Enette (Nutrients, 2019)
The study objective was to validate a food frequency and lifestyle questionnaire (FFLQ) to assess vitamin D intake and lifestyle factors affecting status. Methods: Data collected previously during the fall (n = 86), winter (n = 49), and spring (n = 67) in collegiate-athletes (Study 1) and in active adults (n = 123) (Study 2) were utilized. Study 1: Vitamin D intake and ultraviolet B exposure were estimated using the FFLQ and compared to serum 25(OH)D concentrations via simple correlation and linear regression modeling. Study 2: Vitamin D intake from food was estimated using FFLQ and compared to vitamin D intake reported in 7-Day food diaries via paired t-test and Bland–Altman analysis. Results: Study 1: Serum 25(OH)D was not associated with vitamin D intake from food, food plus supplements, or sun exposure, but was associated with tanning bed use (r = 0.39) in spring, supplement use in fall (r = 0.28), and BMI (body mass index) (r = −0.32 to −0.47) across all seasons. Serum 25(OH)D concentrations were explained by BMI, tanning bed use, and sun exposure in fall, (R = 0.42), BMI in winter (R = 0.32), and BMI and tanning bed use in spring (R = 0.52). Study 2: Estimated Vitamin D intake from food was 186.4 ± 125.7 via FFLQ and 148.5 ± 228.2 IU/day via food diary. There was no association between intake estimated by the two methodologies (r = 0.12, p < 0.05). Conclusions: FFLQ-estimated vitamin D intake was not associated with serum 25(OH)D concentration or food-record-estimated vitamin D intake. Results highlight the difficulty of designing/utilizing intake methodologies for vitamin D, as its status is influenced by body size and both endogenous and exogenous (dietary) sources.